Implementation of the Kirkpatrick Model in Evaluating the Use of Digital Technology in Counseling Guidance Programs at SMP Negeri 1 Matan Hilir Utara - Rahmi Mayarani; Urai Salam; Luhur Wicaksono (Publikasi Indonesia, 2024)
This research aimed to evaluate the Guidance Counseling (BK) service program in the use of digital technology at SMP Negeri 1 Matan Hilir Utara using the Kirkpatrick Evaluation Model. This research method was quantitative with a descriptive approach. Data is technically collected using questionnaire techniques which are the main data source. The subjects in the research were 60 class VIII students who were determined based on a saturated sampling technique where all members of the population were used as research samples. In the context of this research, students act as evaluators or beneficiaries, while the guidance and counseling teachers and school principals are the parties who evaluate the guidance and counseling program services that are implemented. The results of the research show that: 1) At the reaction level, BK services are perceived as showing a scale using digital technology that is on a medium scale with an average of 3.35, 2) At the learning level, BK services in terms of technology use obtain an average of 3. 57 in the high category, 3) At the behavior level with indicators of application of values in the program it is in the medium category with an average of 3.38 in aspects of technology use that need special attention to be optimized, 4) At the results level, students assume that the use of technology is in the medium category with an average of 3.35 which needs to be maximized to improve the quality of the BK program at the research location.